2020
DOI: 10.1111/ane.13289
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological impairments in multiple sclerosis—Central and peripheral motor pathways

Abstract: A systematic review of the literature was conducted comparing neurophysiological outcomes in persons with multiple sclerosis (PwMS) to healthy controls (HC), in studies of the central nervous system (CNS) function comprising motor evoked potentials (MEP) elicited by transcranial magnetic stimulation (TMS) and in studies of the peripheral nervous system (PNS) function comprising electroneuronography (ENG) outcomes elicited by peripheral nerve stimulation. Studies comparing neuromuscular function, assessed durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 82 publications
(194 reference statements)
1
19
0
Order By: Relevance
“…Although these studies have been able to characterize differences in motor function between people with MS and healthy controls, they typically fail to capture the substantial influence of the extra demands on the nervous system of persons with MS when performing prescribed tasks. 33,[117][118][119][120][121][122][123][124][125][126][127] Critically, the reduced capacity of the central nervous system in persons with MS to generate an adequate level of voluntary activation is significantly correlated with the self-reported level of fatigue. 71,121,128,129 One example of this effect is shown in Figure 3, which compares the increase in rating of perceived exertion (RPE) for 2 groups of participants during the intermittent fatiguing contractions shown in Figure 2.…”
Section: Perceived and Objective Fatigabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although these studies have been able to characterize differences in motor function between people with MS and healthy controls, they typically fail to capture the substantial influence of the extra demands on the nervous system of persons with MS when performing prescribed tasks. 33,[117][118][119][120][121][122][123][124][125][126][127] Critically, the reduced capacity of the central nervous system in persons with MS to generate an adequate level of voluntary activation is significantly correlated with the self-reported level of fatigue. 71,121,128,129 One example of this effect is shown in Figure 3, which compares the increase in rating of perceived exertion (RPE) for 2 groups of participants during the intermittent fatiguing contractions shown in Figure 2.…”
Section: Perceived and Objective Fatigabilitymentioning
confidence: 99%
“…33,[117][118][119][120][121][122][123][124][125][126][127] Critically, the reduced capacity of the central nervous system in persons with MS to generate an adequate level of voluntary activation is significantly correlated with the self-reported level of fatigue. 71,121,128,129 One example of this effect is shown in Figure 3, which compares the increase in rating of perceived exertion (RPE) for 2 groups of participants during the intermittent fatiguing contractions shown in Figure 2. Despite similar declines in MVC force immediately after the 60 intermittent contractions (MS: À16 ± 19 N•m; Control: À13 ± 16 N•m), we found that RPE scores increased more rapidly during the task for MS participants.…”
Section: Perceived and Objective Fatigabilitymentioning
confidence: 99%
“…Multiple sclerosis (MS) is a chronic inflammatory and demyelinating disease affecting myelinated axons in the central nervous system (CNS) and it is the leading cause of nontraumatic disability in young adults (1). Demyelination impairs neural conduction (2)(3)(4)(5) leading to various motor, sensory, sphincter, visual, and cognitive symptoms among others (6).…”
Section: Introductionmentioning
confidence: 99%
“…[14] However, MRI estimates of brain volume, grey matter volume, white matter diffusion, and T2-weighted lesion volumes are over time correlated with clinical disabilities in PwMS. [15] When corticospinal tracts are affected by MS lesions, motor evoked potentials (MEPs) are highly capable of detecting and monitoring clinical and subclinical motor nerve conduction alterations, [16] especially in lower extremities. [17] Multimodal evoked potentials can predict future advancement of neurological disabilities in PwMS.…”
Section: Introductionmentioning
confidence: 99%
“…[17] However, the current knowledge about the use of MEP in determining MS disease course is limited. [16,18] Furthermore, electroneurographic (ENG) studies of the PNS in PwMS are few, variable in methodology, and inconclusive. [16,19] Taken together, no studies could be located examining PNS involvement in walking impaired PwMS and its relationship with Fampridine responsiveness, clinical disability measures, nerve conduction in central corticospinal pathways, and MRI outcomes, which was therefore the purpose of the present study.…”
Section: Introductionmentioning
confidence: 99%